Desarrollo de un trazador de curvas como un caso de aplicación de instrumentos basados en Instrumentación Virtual - Vega y Cols., Juan (2019)
The work presents an application case of a versatile platform based on FPGa that has been validated, its architecture makes possible its reuse and promotes the exchange of the firmware and software that transform it in diverse laboratory electronic instruments. This paper describes an instrument that allows the characterization of semiconductor devices by means of its “i vs. v” curve. a board named rvi (reconfigurable virtual instrument) developed at the mlab of the international centre for Theoretical Physics and a signal adapter board makes the hardware of the system while the software was developed using lazarus. The code to configure the FPGa was making using vhDl. This design is intended to contribute to the rvi project initiated by the ictP in 2006, with developing a virtual instrument in this platform.